Report of the Task Force on Waste to Energy (W to E) - Planning Commission (Planning Commission, 2014)
We, the Members of the Task Force constituted to study technological aspects of Waste to Energy (W to E) projects and propose potentially sustainable models of Municipal Solid Waste (MSW) processing including energy recovery through integrated MSW management in the country, have carefully looked at the current situation of MSW management and various technologies that can be supported at a decentralized and centralized level on Public Private Partnership (PPP) mode to enhance resource recovery and deriving energy and nutrients from waste, after due deliberations have adopted the Report for Submission.
Planning Commission
Planning Commission